Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1111/j.1365-2036.2004.02018.x
|View full text |Cite
|
Sign up to set email alerts
|

How effective are the usual treatments for ulcerative colitis?

Abstract: SUMMARYBackground: Details of the efficacy of the drugs used in ulcerative colitis are not readily available. Methods:We have reviewed all placebo-controlled trials of the commonly used drugs for both induction and maintenance of remission to determine the efficacy and to calculate the numbers needed to treat (NNTs) to achieve a specified benefit for each drug. Results: The drug response rates and the NNTs (with 95% CI) are tabulated for each drug. Conclusion: Corticosteroids give a remission rate of 68% in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 38 publications
(57 reference statements)
2
51
1
1
Order By: Relevance
“…However, especially in Japan where the rate of UC is lower than in Western countries (about 1/10), prognostic studies of UC using such a method need an enormous sample size and would not be realistic. Third, the rate of complete response in the present study may be higher than in some earlier reports [13,27,28,29]. However, the definition of complete response in the present study is different from earlier studies in which the treatment effectiveness of only one medicine is reported.…”
Section: Discussioncontrasting
confidence: 55%
“…However, especially in Japan where the rate of UC is lower than in Western countries (about 1/10), prognostic studies of UC using such a method need an enormous sample size and would not be realistic. Third, the rate of complete response in the present study may be higher than in some earlier reports [13,27,28,29]. However, the definition of complete response in the present study is different from earlier studies in which the treatment effectiveness of only one medicine is reported.…”
Section: Discussioncontrasting
confidence: 55%
“…[4][5][6] Overall, induction of remission has been achieved/reported in approximately half of IBD patients, whereas roughly two-thirds of patients remained in remission at 6-12 months of thiopurine therapy. 5,7,8 Although thiopurines are considered to be effective and relatively safe drugs for maintenance therapy, up to 40%-50% of IBD patients discontinue thiopurine therapy during the course of disease. 9,10 The reason for discontinuation of thiopurine therapy is usually the occurrence of intolerable adverse events, which is reported in 10%-28% of the IBD patients using thiopurines.…”
mentioning
confidence: 99%
“…In previous studies, the role of rectal formulation of BDP in treatment of UC has been evaluated in comparison with 5-ASA or prednisolone sodium phosphate enemas showing similar efficacy for mild or moderate distal disease. [8][9][10][11][12][13][14][15][16][17][18] A standard dose of BDP 5 mg od (1 tablet day) has been established in the study conducted by Rizzello et al 9 In this study, administration of 5 mg or 10 mg daily showed therapeutic equivalence in patients affected by mild to moderate extensive or left-sided UC, whilst morning plasma cortisol level decreased in the 10 mg group without changes in vital signs. Oral BDP at a standard dose has been studied in treatment of active extensive or left-sided UC, either in combination with 5-ASA or alone resulting effective and safe, without signs of pituitaryadrenal function impairment.…”
Section: Discussionmentioning
confidence: 85%
“…[10][11][12][13] Patients who clinically failed to respond to treatment after 2 weeks were considered eligible for this single center prospective study. osteoporosis, history of drug or substance abuse, active gastroduodenal ulcer, moderate or severe hypertension, pregnancy and brestfeeding.…”
Section: Patientsmentioning
confidence: 99%